Response of Deep Subsurface Microbial Community to Different Carbon Sources and Electron Acceptors during ∼2 months Incubation in Microcosms - Purkamo, Lotta; Bomberg, Malin; Nyyssönen, Mari; Ahonen, Lasse; Kukkonen, Ilmo; Itävaara, Merja (Frontiers in Microbiology, 2017)
Acetate plays a key role as electron donor and acceptor and serves as carbon source in oligotrophic deep subsurface. It can be produced from inorganic carbon by acetogenic microbes or through breakdown of more complex organic matter. Acetate is an important molecule for sulfate reducers that are substantially present in several deep bedrock environments. Aceticlastic methanogens use acetate as an electron donor and/or a carbon source. The goal of this study was to shed light on carbon cycling and competition in microbial communities in fracture fluids of Finnish crystalline bedrock groundwater system. Fracture fluid was anaerobically collected from a fracture zone at 967 m depth of the Outokumpu Deep Drill Hole and amended with acetate, acetate+sulfate, sulfate only or left unamended as a control and incubated up to 68 days. The headspace atmosphere of microcosms consisted of 80% hydrogen and 20% CO2. We studied the changes in the microbial communities with community fingerprinting technique as well as high-throughput 16S rRNA gene amplicon sequencing. The amended microcosms hosted more diverse bacterial communities compared to the intrinsic fracture zone community and the control treatment without amendments. The majority of the bacterial populations enriched with acetate belonged to clostridial hydrogenotrophic thiosulfate reducers and α-proteobacteria affiliating with groups earlier found from subsurface and groundwater environments. We detected a slight increase in sulfate reducers the 68 days of incubation and the microbial community changed significantly during the experiment, but increase in specifically acetate-cycling microbial groups was not observed.